Article RETRACTED due to manipulation by the authors The effect of modification of movement in training on students' swimming competence - Zainal Arifin; R. Boyke Mulyana; Nina Sutresna; Herman Subarjah; La Sawali; Kukuh Wahyudin Pratama; Azhar Ramadhana Sonjaya; Syed Kamaruzaman Syed Ali; Siti Nursyahiirah Hasan; Siti Nursyafiqah Hasan; Aida Mustapha; Muhammad Nazim Razali; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of the research was to determine the effect of movement modification in training on students' swimming competence. The research method used an experimental method with One Group Pre-test-Post-test Design. The population consisted of 71 students. The sample was taken as many as 10 students with purposive sampling technique. The tool used to collect data was the Swimming Competence Questionnaire (SCQ). The data collection technique consists of three parts: First, the initial test with SCQ; Second, treatment with movement modification; and third, the final test with SCQ. The treatment lasted for 16 training sessions, one training session per week, and 120 minutes per session. The training program consisted of warm-up, exercise, and cool-down. Data analysis techniques used, namely normality test, homogeneity test and hypothesis test. Based on the Paired Samples Test output, the Sig. (2-tailed) value = 0.000 was obtained, which is smaller than a = 0.05. Thus, Ho is rejected and Ha is accepted. The conclusion of this study, the provision of modifications in training can significantly affect the swimming competence of students.